Effect Of Ultrasound Guided Superficial Cervical Plexus Block Using Combination Of Bupivacaine And Lidocaine On Intraoperative Opioid Consumption In Tympanomastoid Operations In Adults, Randomized Controlled Study (Journal of Pharmaceutical Negative Results, 2023)
Background The study aims to detect impact of superficial cervical plexus block using combination of bupivacaine and lidocaine on intraoperative opioid consumption in adults ASA classification I-II in 20-45 years age group in tympanomastoid operations less than 4 hours.Methods Adult Patients belonging to ASA I-II in the age group 20-45 years, of either sex undergoing tympanomastoid operation under GA scheduled for operation time from 30 min to 4 hours.90 Consenting patients will be randomly allocated to two groups, (S group n= 45) received GA without SCP block and (B group n= 45) received GA with SCP block.The primary outcome is to record intraoperative opioid consumption .other outcomes include PONV incidence and severity over 24 hour, number of patients required rescue antiemetic, perioperative hemodynamics, postoperative pain (VAS),first analgesic request, ,side effects of drugs used and incidence of complications related to the block.Results Regarding total intraoperative fentanyl consumption in Group S was 181.11±28.78 while in group B was 162.22±26.45 so there was statistical difference between both groups (p value 0.002).PONV incidence and severity were assessed at 5 time points during the perioperative periodWhen leaving the operating room (V0), there was statistical difference between both groups (P value < 0.001).When leaving the post anaesthetic care unit (PACU) (V1) a period between 0 to 2 h postoperative, there was statistical difference between both groups (P value 0.002).4 hours after leaving PACU (V2) a period between 2 to 4h postoperative, there was statistical difference between both groups (P value < 0.001).8 hours after leaving PACU (V3) a period between 4 to 8h postoperative, there was statistical difference between both groups (P value 0.037).24 hours after leaving PACU (V4) a period between 8 to 24h postoperative, there was no statistical difference between both groups (P value 0.245).Regarding need for rescue antiemetics (ondanestron), there was significant statistical difference between two groups (p value <0.001). 34 patients (75.6%) received rescue antiemetics in group S while 14 patients (31.1%) received rescue antiemetics in group B.Regarding need for postoperative analgesia (ketolac and pethidine), there was no significant statistical difference between two groups either regarding ketolac (p value 0.227) or pethidine (p value 0.830).There was no statistical differences between group S and B all over pain assessment times using VAS score it is may be due to subjective nature of the score and personal evaluation of each patient of pain severity.There were no recorded perioperative complications related to the blocks in both groups.Conclusion Ultrasound guided superficial cervical plexus block using combination of bupivacaine and lidocaine reduce intraoperative opioid consumption in adults ASA I-II in 20-45 years age group of either sex undergoing tympanomastoid operations less than 4 hours.List of abbreviations SCP: Superficial cervical plexus, PONV: Postoperative Nausea and Vomiting, US: ultrasound, ENT: Ear ,Nose and Throat, IV ; Intravenous , VAS: visual analogue scale, PACU: post anesthesia care unit, SPSS: Statistical package for social science.Key pointsQuestion Is SCP block reduce total intraoperative fentanyl consumption in adults undergoing tympanomastoid surgeries?Finding US guided SCP block reduce intraoperative opioid consumption in adults ASA I-II in 20-45 years age group of either sex undergoing tympanomastoid operations less than 4 hours.Meaning SCP block reduce intraoperative opioid consumption in tympanomastoid operations.